2002
DOI: 10.1046/j.1365-2850.2002.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving serious mental illness through interprofessional education

Abstract: Current health policies emphasize partnership between professional groups, between agencies and with users, to ensure more integrated health and social care services. However, a number of reasons have been consistently identified as inhibiting interprofessional working. Among the many factors identified are poor communication, conflicting power relations and role confusion, and these present immense challenges to those who wish to offer interprofessional education and training opportunities. East Gloucestershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 15 publications
1
29
0
2
Order By: Relevance
“…Benefits to patients • Improved social functioning and life satisfaction [17] [17]; six studies demonstrated adequate alignment between the objectives of the study and the reported outcomes, although their research designs were less rigorously described [1,7,13,14,25,27]. Despite this heterogeneity, we found evidence that students of mental health responded well to IPE, especially in terms of more positive attitudes toward the contribution of other professions [1,7,13,14,17,25] and increased knowledge of and skills in collaboration [1,7,13,14,17,26]. However, we found no substantial evidence of changes in behavior or organizational practices, which possibly reflects the complexity of IPE interventions and attitudinal differences toward IPE stemming from differences in work culture, as has also been found by other review studies [3,[28][29][30].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Benefits to patients • Improved social functioning and life satisfaction [17] [17]; six studies demonstrated adequate alignment between the objectives of the study and the reported outcomes, although their research designs were less rigorously described [1,7,13,14,25,27]. Despite this heterogeneity, we found evidence that students of mental health responded well to IPE, especially in terms of more positive attitudes toward the contribution of other professions [1,7,13,14,17,25] and increased knowledge of and skills in collaboration [1,7,13,14,17,26]. However, we found no substantial evidence of changes in behavior or organizational practices, which possibly reflects the complexity of IPE interventions and attitudinal differences toward IPE stemming from differences in work culture, as has also been found by other review studies [3,[28][29][30].…”
Section: Discussionmentioning
confidence: 86%
“…Eight studies reported attitudes toward other professions (level 2a in Kirkpatrick's models of evaluation). Six studies reported change in knowledge and skills [1,7,13,14,17,26]; three studies reported behavior changes that enhanced collaboration [17,25,27]. Changes in organizational practice [1,17,27] were reported in three studies, while only two reported outcomes related to patients' benefit [17,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations